2007
DOI: 10.1152/japplphysiol.00578.2007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of concentric and eccentric resistance training on architectural adaptation in human quadriceps muscles

Abstract: Studies using animal models have been unable to determine the mechanical stimuli that most influence muscle architectural adaptation. We examined the influence of contraction mode on muscle architectural change in humans, while also describing the time course of its adaptation through training and detraining. Twenty-one men and women performed slow-speed (30 degrees /s) concentric-only (Con) or eccentric-only (Ecc) isokinetic knee extensor training for 10 wk before completing a 3-mo detraining period. Fascicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

63
465
17
13

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 428 publications
(558 citation statements)
references
References 61 publications
63
465
17
13
Order By: Relevance
“…We expected eccentric NH strength training to increase hamstring muscle fascicle length, as shown previously with eccentric strength training (Alegre et al 2006;Blazevich et al 2007;Potier et al 2009;Baroni et al 2013;Bourne et al 2016). However, fascicle length did not increase in the NH training group, possibly due to the joint positions assumed during training.…”
Section: Effects Of Nordic Hamstring Strength Training On Muscle Archsupporting
confidence: 69%
“…We expected eccentric NH strength training to increase hamstring muscle fascicle length, as shown previously with eccentric strength training (Alegre et al 2006;Blazevich et al 2007;Potier et al 2009;Baroni et al 2013;Bourne et al 2016). However, fascicle length did not increase in the NH training group, possibly due to the joint positions assumed during training.…”
Section: Effects Of Nordic Hamstring Strength Training On Muscle Archsupporting
confidence: 69%
“…In the past few years, some studies (Blazevich et al, 2007;Duclay et al, 2009;Potier et al, 2009;Reeves et al, 2009) have reported longitudinal growth in human muscles from 7% to 34% in response to eccentric exercise. However, to our knowledge, there is only one study (Butterfield and Herzog, 2006) that investigated the fiber kinetics during eccentric contractions and this was on rabbit muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, resistance training (RT) is frequently employed when aiming to: improve athletic performance (Wilson et al 1996;Comfort et al 2012); enhance mobility of middle-aged and older adults (Brochu et al 2002;Brandon et al 2003); reduce injury risk (Brooks et al 2006;Noyes and Barber Westin 2012); prevent or slow the progression of joint degeneration (Zhang and Jordan 2010). On a cohort level, neural (agonist activation, Komi et al 1978;Narici et al 1996;Tillin et al 2011Tillin et al , 2011antagonist co-activation, Carolan and Cafarelli 1992;Häkkinen et al 1998) andmorphological (hypertrophy, O'Hagan et al 1995;Tracy et al 1999;Erskine et al 2010a; muscle architecture, Aagaard et al 2001;Seynnes et al 2006;Blazevich et al 2007) adaptations have been widely documented to occur after RT and are presumed to explain the observed improvements in strength. However, on an individual basis there is great variability in the changes in strength after RT (Folland et al 2000;Hubal et al 2005), and relatively little is known about the contribution of specific physiological mechanisms to these individual changes, including which is the most important adaptation for determining strength gains.…”
Section: Introductionmentioning
confidence: 99%